Anthology of italian song of the seventh and eighteenth centuries Volume I vol. 290 - PARISOTTI, Alessandro (G. Schirmer. Inc., 1880)
Vittoria, mio corenIntorno all'idol mionChe fiero costumenO cessate di piagarminSe florindo e fedele